Impact of yeast derivatives to increase the phenolic maturity and aroma intensity of wine - Christoph Patauner; Christof Sanoll (Laimburg Journal, 2021)
To increase the aroma of white wine through viticultural or oenological methods is a challenge for every wine producer. The same applies to the increase in phenolic maturity and color intensity in red wine. These two requirements play a decisive role in vintages for which there is a risk of growing grapes with insufficient ripeness. In the wine industry, products made from selected yeast derivatives have recently been offered. These specially developed yeast derivatives are applied two times to the entire foliage. The first, when the berries soften and the second at an interval of 10-14 days. What exactly is caused by these yeast derivatives is not fully recognized. According to the manufacturer, they should generally intensify the wine aroma of white grape varieties and improve the phenolic ripeness of red grape varieties. With this project, this possibility of increasing the aroma and improving the phenolic structure was tested and the extent of the change was measured. The product LalVigne® Aroma from Lallemand was tested on neutral and aromatic white wine varieties, while the product LalVigne® Mature from Lallemand was tested on structured red wine varieties.